Islam as Religion and Culture: Study of the Thought of Sheikh Muhammad Al-Ghazali - Aniq Khoridatun Ni`mah (Konsultan Jurnal Ilmiah Indonesia, 2026)
This article examines the close relationship between Islam as a religion and culture as a social product of human life. Islam is understood not merely as a system of beliefs, but also as a comprehensive way of life that shapes patterns of thought, behavior, and the social structure of its adherents. By examining the thought of Shaykh Muhammad al-Ghazālī, this study demonstrates how Islam is able to interact with culture without losing its fundamental principles. Using a historical-philosophical approach, the research explores al-Ghazālī’s intellectual background, his methodological framework in understanding the Qur’an and the Sunnah, as well as his ideas on tajdīd (renewal). The findings indicate that al-Ghazālī offers a model of Islamic understanding that is moderate, rational, and responsive to contemporary developments. For him, renewal does not mean altering religious teachings, but rather revitalizing Islamic values so that they can address the moral, social, and intellectual challenges faced by the Muslim community. This article affirms that harmony between religion and culture is a key foundation for the formation of a civilized, adaptive, and progressive Muslim society.